Tıbbi gereklilikler ve etik: Öncelik nasıl belirlenmeli? - (:unkn) unknown (My University, 2007)
Bilinci açık, oryante ve koopere bir hastanın kendi isteği ile tedaviyi kabul etmemesi durumunda yasal olarak o hastaya zorla tedavi verilemez. Tüm tıbbi girişimlerde olduğu gibi acil servisteki hasta müdahalelerinde de hasta ya da ailesinin onamı gerekmektedir. Yalnızca psikiyatrik hastalarda bu konuda tartışmalar yaşanmaktadır. Bu hastaların aydınlatılmış onamları konusunda soru işaretleri vardır. Tüm tedavi önerilerini reddeden hastaya başka alternatif yöntemleri de sunulmalıdır. Sunduğumuz olgu intihar girişiminde bulunan ve tedaviyi reddeden bir hasta hakkındadır. Tedavi kararının etik yönünün tartışılmaya ihtiyacı vardır.

According to the laws, a patient who is conscious, oriented and cooperating has a legal right to refuse the therapy. The patient or the family consent is necessary for all the procedures in the emergency room as well as the other medical services. There is, however, some conflict in regard with this problem in the psychiatric patients. Questions still exist about the confirmed consent forms of this patient group. A physician may provide alternative therapy choices for the patients who refuse to be treated in the conventional way. The patient we present here has attempted to commit a suicide and refused any treatment. The ethical issue of the treatment decision needs to be discussed.
Medical necessitıes and ethics: Which comes first?
Keywords: Tıbbi Etik